Collagen architecture in triple negative breast cancer - Zoë Dinkel; Adam Baker; Alannah Akins; Kylie L. King; Matthew Harrington; Deborah Kunkel; Zhi Gao; Tong Ye; Heather Dunn (PLoS ONE, 2025)
This study evaluated collagen properties in TNBC samples collected from different racial groups to determine the presence of variance in matrix architecture. African American (AA) breast cancer patients have a significantly higher mortality rate and nearly a three-fold increased prevalence of triple negative breast cancer (TNBC) when compared to Caucasian (C) patients. The extracellular matrix region surrounding tumors contains abundant collagen fibers, and these fibers undergo remodeling throughout cancer progression, promote metastasis, and impede treatment response. High mammographic density, commonly known as dense breast tissue, is hypothesized to be more prevalent in AA women and characterized by increased collagen deposition and associated with more aggressive cancers. The aim of this research was to investigate fibrillar collagen architecture in TNBC samples from AA and C patients using two-photon microscopy with second harmonic generation (SHG), an intrinsic optical signal produced by fibrillar collagen. Twenty tissue regions per tumor sample were randomly selected for SHG microscopy, and image processing was conducted using the Fiji macro TWOMBLI to quantify mesoscopic fibrillar morphological properties and nanoscopic fibrillar properties with the Forward-Backward SHG ratio. Compared to the images from C tumor samples, those from AA samples exhibited a significant increase in parameters including fiber area, total length, and number of endpoints and branchpoints, but had decreased lacunarity. Collagen microstructure, including fibril arrangement and packing density, did not significantly differ between the groups. These results illustrate that the TNBC samples analyzed from AA patients may have macrostructural collagen characteristics associated with aggressive phenotype tumor formation.